Out-of-school Science Experiences and Interest in Science of Upper Primary School Pupils of Kerala - Gafoor, K. Abdul; Narayan, Smitha (JOURNAL OF INDIAN EDUCATION, 2010)
This study explored out-of-school science experiences and interest in science of upper primary school pupils of Kerala. Data collection made use of Lickert-type scales on topics chosen from the Science curriculum and Science-related experiences that pupils indulge in their daily life. Percentage analysis revealed moderate extent of out-of-school science experiences and relatively high interest in science. Mean difference analysis showed that significant difference existed among pupils in the extent of out-of-school science experiences and interest in science based on gender, locality and type of management of school. The results indicate that in order to reduce disparity among pupils in opportunity to learn teachers need to know about what experiences pupils bring to classroom, monitoring interest should begin from primary classes itself to reduce transitional problems at later stages of study and policy makers and curriculum planners should cater to the special needs of girls as well as rural and aided school pupils.